Atomic habits : tiny changes, remarkable results : an easy & proven way to build good habits & break bad ones - Clear, James (New York : Random House, 2018)
In this ground-breaking book, the author reveals exactly how these minuscule changes can grow into such life-altering outcomes. He uncovers a handful of simple life hacks (the forgotten art of Habit Stacking, the unexpected power of the Two Minute Rule, or the trick to entering the Goldilocks Zone), and delves into cutting-edge psychology and neuroscience to explain why they matter. Along the way, he tells inspiring stories of Olympic gold medallists, leading CEOs, and distinguished scientists who have used the science of tiny habits to stay productive, motivated, and happy.
Includes bibliographical references and index.
ne 23/08/2022
Loans
Keywords: Habit; Habit breaking; Behavior modification